LOW-TEMPERATURE SYNTHESIS OF LEAD ZIRCONATE TITANATE (PZT) POWDER FROM METAL ALKOXIDES - Silvester Tursiloadi; Hiroaki Imai; Hiroshi Hirashima (Jurnal Kimia Terapan Indonesia, 1995)
PZT powder precipitate has been prepared by hydrolyzing a mixture of lead di-i-propoxide, zirconium tetra-n-butoxide and titanium tetrai-propoxide. The crystallization process of the amorphous PZT was studied by means of X-ray diffraction analysis. It was found that the powder precipitate was still amorphous on heating until 400°C for 2k As an intermediate product, metastable cubic Pb2Ti2O6 (pyrochlore phase) was found after heating at 450°C for 2h. In addition to Pb2Ti206 peaks, the diffraction peaks of perovskite PZT phase were observed after heating at 430°C for 24 h. After heating at 600 °C for 2h, only diffraction peaks of tetragonal perovskite PZT phase were found. The lattice parameters of the tetragonal PZT have been obtained to be a=4.066 A c=4.196 A This tetragonal perovskite phase was stable on heating until 1000 "C. The density of the compacted powder precipitate after heating at 1000°C (a relatively low temperature for the sintering of PZT) for 30 min. was 6.1 g/cm3, about 76% of the theoretical value.